(untitled) (Sains Humanika, 2019)
Health education tools are important to stimulate responses and facilitate interaction among the participants during health education and counseling sessions. In addition to brochures, pictures and charts, exemplar is one of the most useful tools to engage participants during the sessions. Exemplar refers to a narrative or a story that elaborates on a personâ€™s personal experience. The present study aims to examine the effects of exemplar (first and third person), message appeals (fear and motivational appeals) on the intention to stop smoking through the mediating role of narrative engagement. The study utilized a 2x2 between-subjects field experiment conducted among 16 counselling groups (with ten members in each group) who registered for the Stop Smoking Clinics under the Ministry of Health Malaysia. The result showed significant main effect of exemplars, message appeals and interaction effect of both variables on the intention to stop smoking. Narrative engagement was also found to play a significant mediating role in increasing Â the intention to stop smoking. The study concludes that the use of the first person exemplars with fear appeal will lead to greater narrative engagement and eventually stronger intention to stop smoking. Findings derived from the study would assist health education practitioners in choosing the most effective exemplars that can be used in health counseling sessions. Â